基于NARX神经网络的交直流电网自治能力评估方法 (2022)
本发明提供了一种基于NARX神经网络的交直流电网自治能力评估方法，从源网荷储角度，提取训练交直流电网数据的分项评估指标；根据分项评估指标，确定原始评价矩阵及参考数列；使用熵值法，确定各分项评估指标的客观权重；根据原始评价矩阵、参考数列和客观权重，确定训练电网数据的综合灰关联度；根据分项评估指标和综合灰关联度，训练NARX神经网络的评估模型；基于训练的NARX神经网络的评估模型，评估交直流电网自治能力等级。本发明比传统方法选取的指标特征更具全局性，评估精度更高。 The invention provides an AC/DC power grid autonomous capability evaluation method based on an NARX neural network, and the method comprises the steps: extracting sub-item evaluation indexes of training AC/DC power grid data from the perspective of source grid load storage; determining an original evaluation matrix and a reference sequence according to the subitem evaluation indexes; determining an objective weight of each subitem evaluation index by using an entropy method; determining a comprehensive grey correlation degree of the training power grid data according to the original evaluationmatrix, the reference sequence and the objective weight; training an evaluation model of the NARX neural network according to the sub-item evaluation indexes and the comprehensive grey correl